The Drosophila blood-brain barrier: development and function of a glial endothelium - Limmer, Stefanie; Weiler, Astrid; Volkenhoff, Anne; Babatz, Felix; Klämbt, Christian (Frontiers in Neuroscience, 2014)
The efficacy of neuronal function requires a well-balanced extracellular ion homeostasis and a steady supply with nutrients and metabolites. Therefore, all organisms equipped with a complex nervous system developed a so-called blood-brain barrier, protecting it from an uncontrolled entry of solutes, metabolites or pathogens. In higher vertebrates, this diffusion barrier is established by polarized endothelial cells that form extensive tight junctions, whereas in lower vertebrates and invertebrates the blood-brain barrier is exclusively formed by glial cells. Here, we review the development and function of the glial blood-brain barrier of Drosophila melanogaster. In the Drosophila nervous system, at least seven morphologically distinct glial cell classes can be distinguished. Two of these glial classes form the blood-brain barrier. Perineurial glial cells participate in nutrient uptake and establish a first diffusion barrier. The subperineurial glial cells form septate junctions, which block paracellular diffusion and thus seal the nervous system from the hemolymph. We summarize the molecular basis of septate junction formation and address the different transport systems expressed by the blood-brain barrier forming glial cells.